PENGARUH KEBEBASAN DALAM BEKERJA, LINGKUNGAN KELUARGA DAN KEBERANIAN MENGAMBIL RISIKO TERHADAP MINAT BERWIRAUSAHA - Alit Hidayatul Azmi; N. Rachma; Alfian Budi P (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted at University of Islam Malang which is located at Jalan Mayjen Haryono 193 Malang. The purpose of this study was to examine and analyze the influence of freedom of work, social environment and the courage to take risks on the interest in entrepreneurship of the student faculty of islam Malang.The variables in this research is freedom of work, social environment and the courage to take risks as an independent variable and the interest in entrepreneurship as dependent variable in this research. The sample used in this research is was 95 students of economics faculty of islam malang. The study was uses explanatory research. Data collection method by shareing the questioner. The analysis used includes instrument testing, classical assumption tests, normality tests, multiple linear regression, hypothesis testing and coefficient of determination tests using multiple regression analysis using SPSS. The result of this study showed that the freedom of work and courage to take risks is significantly influence the interest of entrepreneurship while social environment did not significantly influence the interest of entrepreneurship student of economics faculty of islam malang. Keyword : freedom of work, social environment, the courage to take risks and interest in entrepreneurship